Hypothyroidism in type 2 diabetic patients: a tertiary care hospital experience - Qureshi, Nazmul Kabir; Aktaruzzaman, AHM; Amin, Md Ruhul; Nahid, Khan Lamia; Pathan, Md Faruque (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Hypothyroidism is one of the most common endocrine disorders encountered in endocrine practice worldwide which is more prevalent in elderly and women and its prevalence varies according to population studied. Both type 1 and type 2 Diabetic patients have higher prevalence of hypothyroidism than normal population not for direct etiology rather due to autoimmune association and increasing age. Co-existing hypothyroidism may impose co-morbid effects of dyslipidemia, atherosclerosis, hypertension and renal impairment on diabetic patients. Objective This study was designed to find out frequency and association of clinical and sub-clinical hypothyroidism in adult type 2 diabetic subjects. Method This was a cross sectional study conducted during the period of December 2009 to November 2010 in a tertiary care specialized hospital, (BIRDEM). Thyroid hormone (FT4 and TSH) was studied among 227 adult type 2 diabetic subjects. Results Among 227 study subjects, female respondents were 67%. Age (in years) was as mean± SD (SE) and (95% CI): 53.95±11.6 (.77) and (52.44-55.47). Thyroid hormone (FT4 and TSH) was assayed. FT4 (in pmol/L) of this population was as mean± SD (SE) and (95% CI): 13.05±2.66 (.18) and (12.71-13.4) and TSH was (in μIU/ml) as mean± SD(SE) and (95% CI): 4.12±7.03(.47) and (3.2-5.04). Sixty nine (30.4%) of them were hypothyroid and rest 158 (69.6%) were euthyroid. Among the hypothyroid cases, 17.6% were cases of sub-clinical hypothyroidism and 12.8% were of clinical hypothyroidism. Conclusion Diabetic population have higher prevalence of hypothyroidism. While planning therapeutic approaches for diabetic patients, clinical and sub clinical hypothyroidism always should be taken into consideration. Diabetic patients with or without complication particularly with poor glycemic control, should be routinely screened for hypothyroidism. JBSA 2012; 25(1): 14-20